Effects of consuming a Malaysian acacia honey drink prior to, during and post exercise on physiological responses, blood glucose metabolism, urine osmolality and running timetrial performance in the heat - Kiew, Ooi Foong (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2019)
This study investigated the effectiveness of Malaysian Acacia honey drink ingested before, during and post exercise on physiological responses, blood glucose metabolism, urine osmolality and running time-trial performance in the heat. The first phase of this study found that honey drink and sports drink ingestion before and during exercise elicited similar effects on physiological responses, blood parameters and running performance in the heat. The second phase of the study found that honey drink during dehydration after exercise elicited benefiCial effect on running performance and selected physiological parameters. Therefore, Acacia honey drink, a local Malaysian product, can be proposed to be used as an alternative ergogenic aid before, during and post exercise for athletes who train and compete in hot environment.